"It's a Win-Win Situation" – Intergenerational Learning in Preschool and Elder Care Settings: An Irish Perspective: Practice. Issue 1 (3rd April 2018) - Gallagher, Carmel; Fitzpatrick, Anne
ABSTRACT: This paper explores the level and sustainability of intergenerational practice in early years and elder care settings in Ireland. The paper is based on a small-scale research study involving interviews with staff in five organizations and builds on findings from previous research conducted for the TOY project (http://www.toyproject.net ). The paper examines the pedagogies involved as well as the community context of intergenerational practice in early years and elder care settings. The findings highlight that sustainable intergenerational practice is facilitated by strong pedagogies that support active and relational learning across the life course and by being embedded in robust community networks.